Facilitators and obstacles to innovation in public management: perceptions of public officials in local governments, Chiloe Province, Chile - España-Ruiz, Rodrigo; Rivera Cubillos, Daniela; Rivera-Mercado, Claudio; Mondaca Mansilla, Eduardo; Zahn Muñoz, Cristian (Revista del CLAD Reforma y Democracia, 2025)
This article assesses the perceptions of public officials in local governments in Chile regarding public innovation. Special emphasis is placed on their disposition toward innovation and the identification of facilitators and barriers to innovation in the public sector in general, and in municipalities in particular. The study comprised a case study in the Chiloe archipelago, Chile, employing a mixed-methods approach that included documentary analysis and a questionnaire administered to local government leaders. The results indicate a high level of knowledge about public innovation and a high willingness to participate in innovative initiatives. The main facilitators and barriers of public innovation were identified. Among the former, the political will of the authorities and investment in innovation stand out; among the latter, the burden of regular administrative work and the lack of skills to manage innovation stand out. Differences were found in the responses regarding the facilitators and barriers of innovation by gender and municipal size. The study contributes to a deeper understanding of the dynamics of public innovation in local public administrations in Chile, contributing empirical information to the debate on public innovation.
Keywords: Public Innovation; public management; local government; Chiloe; facilitators; barriers